Implementation of Coal Mining Company CSR Program towards Sustainable Livehood - Nurul Yakin (Ridwan Institute, 2023)
This study aims to determine the implementation of Corporate Social Responsibility (CSR) programs in coal mining companies and their impact on sustainable livehood. This research uses a qualitative descriptive approach to produce reliable and valid data and information. Data collection techniques use interviews, observations and discussions. The source of the data is a key informant taken by snowball sampling method from the company, government and community. The data was analyzed using interactive methods. The results showed that the implementation of Corporate Social Responsibility (CSR) Programs has not been carried out optimally. There are still problems in economic development, land acquisition and the environment, resulting in conflicts between the community and companies, governments and communities.